Criblage de génotypes de manioc (Manihot esculenta CRANTZ) pour la résistance à la cochenille Africaine de racines et tubercules (Stictococcus vayssierei Richard) dans différentes zones agro-écologiques de Beni (Nord Kivu, RD Congo) - Ndengo, N.E.; Ki-Munseki, A.L.; Hanna, R.; Ngbolua, K. (2016)
Cassava is, economically, one of the most important root and tuber crops in Africa. However, its production is compromised by a large number of diseases and pests among which the african root and tuber scale (Stictococcus vayssierei Richard). This insect causes damage that can result in a low yield and non tuber formation of cassava in case of serious infestation. It is in this context that a study on screening cassava (Manihot esculenta CRANTZ) genotypes was carried out for resistance to African root and tuber scale in different agro ecological areas of Beni (North Kivu province, in East of the Democratic Republic of Congo). The objective of the study is to assess resistance to African root and tuber scale of 40 varieties of cassava supplied by the International Institute of Tropical Agriculture and the National Institut of Research Agriculture whose five local are found on the spot after survey. To reach this goal, we verified the hypothesis that stipulates that the introduction of new varieties of cassava in the country is a strategy to fight African root and tuber scale. All varieties were placed in four sites under mild altitudes (1000-1200 m) and high altitudes (1200-1400 m). The populations of African root and tuber scale in various stages of life and the tuberous root production of each variety were assessed every three months for two years in a randomized block experimental with four repetitions. The screening ANOVA findings showed significant effects, S. vayssierei infested the majority of tested varieties. Nevertheless, principal components analysis (PCA) and cluster analysis identified a reconciliation of tolerance vis-à-vis African root and scale in some improved varieties while released viz, Liyayi (MM96/0287), Obama (TME 419), Mvuazi (I95/528), Dinsaka (I96/0211) and while developing such as 20BI, 20B2, 20B4, 20B16, 20B27, 20B28, 20B29, 81, MM96/0105, MM96/4653, MM96/5272, MM96/5475, MM97/2206 as well as on some local varieties such as MUKAKASA, MBAYILO in different agro ecological areas of Beni Territory in view of the marketable tuberous root production at the end of screening. All the above-mentioned varieties gave a yielded ranging from 20, 3 T/ha to 74, 96 T/ha, included or over the interval acceptable by officially released varieties in DRC. The results indicated that the introduction of improved cassava varieties could be one of the alternatives for African root and tuber scale integrated management. Also, they show the importance of local varieties research for the development of cassava subsector.